Prevention and treatment of decompression sickness using training and in-water recompression among fisherman divers in Vietnam - Blatteau, J.; Pontier, J.; Buzzacott, Peter; Lambrechts, K.; Nguyen, V.; Cavenel, P.; Ruffez, J. (B M J Group, 2016)
© 2016 BMJ Publishing Group. All rights reserved. Introduction Many fisherman divers in Vietnam suffer from decompression sickness (DCS) causing joint pain, severe neurological deficit or even death. The objective of this pilot study was to evaluate the effectiveness of a training programme to prevent DCS and also treat DCS using the method of in-water recompression (IWR). Methods 63 divers were interviewed and trained over a period of 3 years from 2009. Fifty one per cent of all trained divers were reinterviewed in 2011–2012 to collect mortality and morbidity data as well as information on changes in diving practices. Results Since 2009, most fisherman divers have changed their practices by reducing bottom time or depth. Mortality was reduced and the incidence of severe neurological DCS decreased by 75%. Twenty four cases of DCS were treated by IWR. Ten cases of joint pain were treated with IWR using air, affording immediate relief in all cases. Out of 10 cases of neurological DCS, 4/4 recovered completely after IWR with oxygen whereas only 2/6 subjects recovered immediately after IWR with air. In addition, 3/4 further cases of DCS treated with IWR using oxygen immediately recovered. Conclusions Our results suggest that IWR is effective for severe neurological DCS in remote fishing communities, especially with oxygen.